2017
DOI: 10.1155/2017/7910432
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Cellular Changes in the Bone Marrow following PTH(1-34) Treatment of OVX Rats Using a Portable Stray-Field NMR Scanner

Abstract: Osteoporosis is characterized by reduction in trabecular bone in conjunction with increased marrow cell adiposity. While these changes occur within weeks, monitoring of treatment efficacy as performed by DEXA is sensitive only to long-term changes. MRI is sensitive to bone marrow changes but is less affordable. In a recent study, we have shown that a stray-field NMR can monitor bone marrow cellular changes that are related to osteoporosis. Objectives. To demonstrate sensitivity of a low-field tabletop NMR scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Previous investigations have made the link between the marrow microenvironment and bone remodeling (8,19,24,28), suggesting paracrine signaling between bone marrow and bone cells. For example, restoration of hematopoietic stem cells in the tibia following intermittent PTH administration in mice served to augment bone volume (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations have made the link between the marrow microenvironment and bone remodeling (8,19,24,28), suggesting paracrine signaling between bone marrow and bone cells. For example, restoration of hematopoietic stem cells in the tibia following intermittent PTH administration in mice served to augment bone volume (28).…”
Section: Discussionmentioning
confidence: 99%
“…), the numbers of hematopoietic stem cells and adipocytes were partially increased and decreased, respectively, compared with the Bmi1null, vehicle-treated animals (28). Furthermore, PTH 1-34 administration suppressed and prevented adipogenesis in the marrow microenvironment of ovariectomized rats (19). Thus, it is speculated that intermittent PTH administration modulates the accessory cells in the marrow (24), which may contribute to bone accrual.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A possible mitigation strategy may be the use of low-cost low-field MRI systems. Indeed, Sarda et al and Hillel et al [ 19 , 20 ] used animal models and suggested that stray field NMR can be used to detect changes in bone marrow composition, potentially enabling screening and treatment follow-up [ 19 , 20 ]. Importantly, translation of such works to humans requires a target bone that can easily be probed using such scanners.…”
Section: Introductionmentioning
confidence: 99%